Pengaruh Penggunaan Smart Phone pada Perkembangan Anak Balita di Wilayah Puskesmas Kelurahan Rawa Badak Selatan, Jakarta Utara - Nessi Meilan; Willa Follona; Yudhia Fraditina (FORUM ILMIAH KESEHATAN, 2019)
In 2018, the number of active smartphone users in Indonesia is more than 100 million, while the population is 250 million. Smartphones can be operated with the touch of a finger, so babies and children who find it difficult to use a laptop can easily and comfortably use a smartphone. The behavior of using a smartphone during the